Kejahatan Siber Hoax di Ruang Digital Masyarakat Indonesia melalui Teori Aktivitas Rutin - Micah Davis Mahardika (Jurnal Kriminologi Indonesia, 2020)
AbstractThe discussion in this paper focuses on looking at data related to fake news and hoaxes that statistically continue to rise in the digital space of society. The analysis carried out on the deliberate making of fake news and hoaxes by certain parties provides an overview of their impact empirically and concretely on the views and paradigms of netizens or the internet community in Indonesia. The journal that is the source of the literature review is research that discusses the impact of hoaxes in different contexts, times and locations. The author uses the Neo-Routine Activity Theory which is very suitable for analyzing various types of cybercrime. The analysis that has been done concludes that fake news and hoaxes have effectively produced concrete impacts on the digital space of Indonesian society.Keywords: Fake News, Hoax, Cybercrime, Digital Space